Epidemiology of intraocular pressure in a population screened for glaucoma. Issue 10 (October 1987) - David, R.; Zangwill, L.; Stone, D.; Yassur, Y.
Abstract : This study evaluated the association between intraocular pressure and various sociodemographic characteristics, ocular findings, and cardiovascular risk factors in a population screened for glaucoma. A total of 2594 subjects older than 40 years residing in three urban areas of southern Israel participated. Of those screened 6.1% had a raised intraocular pressure (IOP greater than or equal to 21). The mean IOP increased with age, was higher among persons born in Africa or Asia than those born in Europe or America, higher among myopes than hypermetropes and among those with an enlarged cup-disc ratio (CDR). Analysis of variance tests indicated that refractive status, CDR, age, country of birth, and diabetes were each independently associated with IOP. In addition, associations between raised intraocular pressure and age, country of birth, myopia, CDR, diabetes, and glaucoma in the family were found.